Examining The Social Drivers Of Entrepreneurship: A Case Of Business Owners In Aboabo Market In Tamale - Abubakari, Abdul-Razak; Samira, Kassim (Archives of Business Research, 2021)
This research examined the social drivers of entrepreneurship among business owners in Aboabo market in Tamale. A quantitative research approach was adopted and the target population was business owners in Aboabo market in Tamale. It was found that not all social drivers that influence decision to become entrepreneurs motivate entrepreneurs to remain in business. Also, family or close relation, belonging to a social club (social capital), previous work experience and social status positively affect business performance while being a married woman and being a woman does not affect entrepreneurial performance. Access to finance, family and friends involvement are major challenges of entrepreneurship whereas lack of social support, low educational background and gender discrimination are not major challenges of entrepreneurship. Based on these findings, the study recommended entrepreneur education, community support and easy access to finance through government intervention to help entrepreneurs relish their full potential to support economic growth and development significantly.